2015
DOI: 10.1093/carcin/bgv046
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interactions among flavonoids and acetogenins in Graviola (Annona muricata) leaves confer protection against prostate cancer

Abstract: Phytochemical complexity of plant extracts may offer health-promoting benefits including chemotherapeutic and chemopreventive effects. Isolation of 'most-active fraction' or single constituents from whole extracts may not only compromise the therapeutic efficacy but also render toxicity, thus emphasizing the importance of preserving the natural composition of whole extracts. The leaves of Annona muricata, commonly known as Graviola, are known to be rich in flavonoids, isoquinoline alkaloids and annonaceous ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 38 publications
0
98
1
10
Order By: Relevance
“…Of the 12 toxicity tests reported, only one study reported behavioural signs of toxicity in mice at an oral dose of 4000 mg/kg in response to aqueous leaf extract which included paw licking, salivation, stretching and reduced activity . In mice studies, the calculated intraperitoneal LD 50 varied from 155 mg/kg for aqueous leaf extract to 1092 mg/kg for ethanolic leaf extract .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 toxicity tests reported, only one study reported behavioural signs of toxicity in mice at an oral dose of 4000 mg/kg in response to aqueous leaf extract which included paw licking, salivation, stretching and reduced activity . In mice studies, the calculated intraperitoneal LD 50 varied from 155 mg/kg for aqueous leaf extract to 1092 mg/kg for ethanolic leaf extract .…”
Section: Resultsmentioning
confidence: 99%
“…While the fruit is traditionally used to alleviate the symptoms associated with neuralgia, arthritis, diarrhea, dysentery, fever, malaria, parasites, rheumatism, skin rashes, and worms, the leaves are believed to have antirheumatic and neuralgic effects [4]. Among various bioactive components in Graviola, annonaceous acetogenins have antiproliferative effects and thus possess potential anticancer properties [23, 24]. The ethyl acetate extract of Graviola leaves inhibited the proliferation of A549 cells and human breast cancer cells by arresting the cell cycle and inducing apoptosis [5, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, acetogenins displayed antioxidant activity and are considered as a therapeutic candidate for treatment of chronic diseases initiated by oxidative stress [6, 26, 27]. Besides, Graviola leaf contains various phytoconstituents such as alkaloids, flavonol triglycosides, phenolics, cyclopeptides, and essential oils [6, 13, 24]. Recently, we found that Graviola contains high concentrations of rutin, kaempferol-rutinoside, and vitamin U and effectively scavenged peroxyl and nitrogen radicals [14].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 47 entries were found for human structural flavonoid/protein complexes and another ~ 65 structural hits for non-human complexes including molecules that synergistically interact with flavonoids to render them effective putative cancer treatment/prevention compounds for specific cancers such as prostate cancer [12]. The complete library is provided as supplemental materials to this review in Appendix A: Flavonoid/Protein Complexes.…”
Section: Selection Of Flavonoid/protein Complexesmentioning
confidence: 99%